Growth and characterization of Ga/F co-doped ZnO nanorods/nanodisks via hydrothermal process - Chongsri, Krisana; Sinornate, Wuttichai; Boonyarattanakalin, Kanokthip; Pecharapa, Wisanu (My University, 2016)
Ga/F co-doped ZnO nanorods/nanodisks (GFZO) were synthesized using a hydrothermal process by varying the Ga doping levels (1-5 wt.%) and F doping levels (1-5 wt.%). Zinc nitrate, gallium nitrate hydrate and ammonium fluoride were chosen as starting precursors for Zn, Ga and F sources, respectively. The nanorod growth was initiated by zinc oxide seeding film fabricated by spin coating on glass substrate using zinc acetate precursor and annealed at 500°C for 2 h. Effect of different dopant concentrations on morphologies, structural, and optical properties of the samples were investigated by X-ray diffraction (XRD), scanning electron microscope (SEM) and photoluminescence spectroscopy (PL), respectively. The results of Ga/F codoped ZnO (GFZO) were compared to the single doped specimens including Ga:ZnO (GZO) and F:ZnO (FZO) samples, and bare ZnO sample. The results suggest that content of either Ga or F dopant has high influence on relevant properties of as-synthesized nanorods/nanodisks.
Keywords: GFZO; Hydrothermal process; Nanodisks; Nanorods